Nutrition management of inherited metabolic diseases : lessons from metabolic university - Bernstein, Laurie E.; Rohr, Fran; Helm, Joanna R. (Springer International Publishing Imprint: Springer, 2015)
This up-to-date reference on the nutrition management of inherited metabolic diseases (IMD) covers a wide range of these disorders, including phenylketonuria and other aminoacidopathies, organic acidemias, urea cycle disorders, fatty acid oxidation disorders, galactosemia, and glycogen storage diseases. Guidance is also provided on laboratory evaluations and biochemical testing and monitoring. Topics such as newborn screening for IMD, as well as nutrition management during pregnancy and transplantation, are addressed. The book is based on 7 years of lectures delivered through Metabolic University - an interactive, didactic program designed to provide training to dietitians who work with individuals with IMD. This book provides the basic information required to manage nutrition care and is a resource for clinicians new to this complex field.